2022
DOI: 10.3389/fpsyg.2022.903920
|View full text |Cite
|
Sign up to set email alerts
|

Music Aptitude, Training, and Cognitive Transfer: A Mini-Review

Abstract: In this mini-review, the genetic basis of music aptitude and the effects of music training are discussed. The review indicates that regardless of levels of innate ability, experience-induced neuroplasticity can occur as a result of music training. When that happens, it can be expressed as functional or structural brain changes. These changes are often accompanied by improvement in performance in tasks involving auditory analysis. Specifically, music training effects can transfer to a closely related cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…32, 33 Patel's OPERA hypothesis suggests this type of transfer can occur because of neural overlap in related substrata, high precision of acoustic processing, recruitment of emotional and attentional resources, and repetitive activation of the neurocognitive network through music practice. 33 Evidence suggests that a range of music-related cognitive functions are enhanced in musicians, 32 and there is also evidence that several cognitive functions in musicians are maintained in older age, with aging musicians exhibiting relatively preserved speech perception 34 and auditory processing ability. 35,36 Similarly, Hanna-Pladdy and Gajewski 37 reported that older musicians exhibit enhanced phonemic fluency, verbal working memory, verbal immediate recall, as well as superiority in visuospatial and motor domains when compared with matched non-musicians.…”
Section: Cognitive Benefits Of Music Engagement Across the Lifespanmentioning
confidence: 99%
See 2 more Smart Citations
“…32, 33 Patel's OPERA hypothesis suggests this type of transfer can occur because of neural overlap in related substrata, high precision of acoustic processing, recruitment of emotional and attentional resources, and repetitive activation of the neurocognitive network through music practice. 33 Evidence suggests that a range of music-related cognitive functions are enhanced in musicians, 32 and there is also evidence that several cognitive functions in musicians are maintained in older age, with aging musicians exhibiting relatively preserved speech perception 34 and auditory processing ability. 35,36 Similarly, Hanna-Pladdy and Gajewski 37 reported that older musicians exhibit enhanced phonemic fluency, verbal working memory, verbal immediate recall, as well as superiority in visuospatial and motor domains when compared with matched non-musicians.…”
Section: Cognitive Benefits Of Music Engagement Across the Lifespanmentioning
confidence: 99%
“…While existing research is often correlational, evidence has been reported that music engagement may confer cognitive benefits in children, as well as healthy younger and middle-aged adults, suggesting that music engagement enhances the ability of people to meet the cognitive demands of certain non-musical tasks. 30 , 32 For example, music-related auditory processing abilities, involved in detecting acoustic cues (rhythm, pitch and timbre), processing syntactic or semantic information, and integrating relevant semiotic meaning (implicit in prosodic patterns) may provide utility to language perception. 32 , 33 Patel’s OPERA hypothesis suggests this type of transfer can occur because of neural overlap in related substrata, high precision of acoustic processing, recruitment of emotional and attentional resources, and repetitive activation of the neurocognitive network through music practice.…”
Section: Cognitive Benefits Of Music Engagement Across the Lifespanmentioning
confidence: 99%
See 1 more Smart Citation